Server less Architectures in Cloud Computing: Evaluating Benefits and Drawbacks - Uday Krishna Padyana; Hitesh Premshankar Rai; Pavan Ogeti; Narendra Sharad Fadnavis; Gireesh Bhaulal Patil (Innovative Research Thoughts, 2024)
A highly efficient computer paradigm for optimising resource usage is emerging: cloud computing. Even with the advantages taken into account, switching to cloud technology is always dangerous from the customer's standpoint. Research on cloud computing that is currently available concentrates on technical issues including efficiency, quality, and security. On the other hand, the actualization of cloud computing is still a very new area of study. The new paradigm of server less computation, which allows developers to provide programmes as stateless functions without consideration for the infrastructure that supports them, is the outcome of recent advancements in virtualisation and software design. Therefore, the lifespan, execution, and scalability of the actual functions—which are only required to run when called upon or triggered by an event—are managed by a server-less system. We present the design of a cutting-edge, performance-focused, server-less computing platform that runs on Microsoft Azure, is built in.NET, and uses Windows container technology for function implementation. Implementation issues are thoroughly investigated, including function scalability and container discovery, longevity, and reuse. We evaluate our prototype and provide metrics for assessing the execution effectiveness of server less platforms, including IBM's Apache Open Whisk implementation, AWS Lambda, Microsoft Azure Functions, and Google Cloud Function. We test the preliminary version and find that it beats competing platforms at most concurrent levels. We also look at the implementations' scalability and instance expiration patterns. In addition, we address the shortcomings and restrictions of our present design, suggest possible solutions, and outline further investigation.